Nitrogen substitution induced lattice contraction in nickel nanoparticles for electrochemical hydrogen evolution from simulated seawater - Singh B.; Singh A.K.; Priyadarsini A.; Huang Y.-C.; Dey S.; Ansari T.; Shen S.; Lahiri G.K.; Dong C.-L.; Mallik B.S.; Indra A. (My University, 2025)
Herein, we demonstrate a facile method for the introduction of nitrogen in the lattices of nickel nanoparticles to form NiNx (x = 0.13, 0.20, 0.27). X-ray absorption spectroscopy reveals the contraction of the Ni-Ni bond and modulated coordination environment after nitrogen introduction. The NiN0.20 required 87 mV overpotential for −10 mA cm−2 cathodic current density in simulated seawater. The density functional theory calculations revealed favorable EH and ΔGH after N-introduction. © 2023 The Royal Society of Chemistry.